Urea hydrolysis in different farmland soils as affected by long-term biochar application - Zhao, Rui; Liu, Juying; Xu, Na; He, Tianyi; Meng, Jun; Liu, Zunqi (Frontiers in Environmental Science, 2022)
Urea is a commonly used nitrogen (N) fertilizer that contributes to world food production, and there have been increasing concerns about relatively low urea-N use efficiency. Biochar has shown the potential to mitigate N loss, but how biochar influences urea hydrolysis and the underlying mechanisms are still unclear. In this study, long-term biochar-amended upland, paddy and greenhouse soils were sampled at depths of 0-20 and 20-40 cm in Haicheng City, Northeast China. Soil N contents, urea hydrolysis rates (UHRs), and total, intracellular and extracellular urease activities were determined, as well as the total bacterial and ureolytic microbial gene abundance were quantified. The results showed that biochar increased total urease activity by 32.64-66.39% in upland soil and by 2.90-2.13-fold in paddy soil. Both intracellular and extracellular ureases contributed to the increase in total urease activity. However, in greenhouse soil, extracellular (+ 35.07-74.22%) and intracellular (- 40.14-77.68%) urease activities responded inconsistently to biochar incorporation. Increases in ureC gene copy numbers (2.15- to 4.47-fold) in upland and greenhouse (20.93%) soil implied that biochar stimulated microorganisms capable of producing urease, and the biochar liming effect increased the soil pH (0.11-0.60 units), which optimized the ureolytic reaction, together explained the increases in urease activity. We found that the decreased soil N content was accompanied by a higher UHR in upland and greenhouse soils, suggesting that the accelerated UHR exerted a negative effect on the soil N content, possibly caused by excessive NH3 volatilization. In paddy soil, where the UHR was not increased, biochar was an effective amendment for simultaneously improving soil urease activity and N content.